Penerapan Model Pembelajaran Kooperatif STAD Untuk Meningkatkan Kemampuan Pemecahan Masalah Siswa Kelas IV SD Negeri Dukuh 1 Sleman - Eko Pranowo; Martalia Ardiyaningrum (Universitas Alma Ata, 2019)
Learning mathematics in 4th grade of SD N Dukuh 1 Sleman still uses a coventional learning model and has not provided opportunities for students to develop problem solving skills. In addition, the achievement of minimum criteria in integer number operation is still not optimal. This study aims to 1) describe the application of STAD cooperative learning to integer concepts; and 2) describe the improvement of problem solving skills in 4th grade students of SD N Dukuh 1 Sleman, academic year of 2014/2015. The method used in this study is a classroom action research method by adopting the Kemmis Mc Taggart model. The subjects of this study were 17 students in 4th grade of SD N Dukuh 1 Sleman. The results of the research obtained showed that STAD cooperative learning in mathematics can improve the problem solving skills of 4th grade students of SD N Dukuh 1 Sleman. In cycle I, the percentage of students who had test scores on problem solving skills was more than 70 at 6%, while in cycle II the percentage obtained was 100%. Based on the percentage above, the problem solving skills of 4th grade students in SD N Dukuh 1 Sleman has increased. The average value test of the cycle I is 53.24 and the cycle II is 87.35. Based on the research results, it can be concluded that STAD cooperative learning can improve the problem solving skills of 4th grade students of SD N Dukuh 1 Sleman.Keywords: learning model, cooperative, STAD, problem solving skills.